2015
DOI: 10.1037/fam0000084
|View full text |Cite
|
Sign up to set email alerts
|

Fostering parents’ emotion regulation through a sibling-focused experimental intervention.

Abstract: In this study, we assessed whether an intervention designed to improve children's sibling relationships, the More Fun with Sisters and Brothers program (MFWSB), may also help parents manage their emotions more effectively. Families with at least 2 children between the ages of 4 and 8 years were randomly assigned to an intervention (n = 50) or wait-list control (n = 34) group. Parents completed pre- and posttest questionnaires on sibling warmth and agonism, their emotion regulation during sibling conflict, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Because ED is very common, especially in children and adolescents (although only in the focus in the last decade), various treatment options primarily concentrate on this dimension (426,(435)(436)(437)(438)(439)(440)(441)(442)(443)(444).…”
Section: Preventionmentioning
confidence: 99%
“…Because ED is very common, especially in children and adolescents (although only in the focus in the last decade), various treatment options primarily concentrate on this dimension (426,(435)(436)(437)(438)(439)(440)(441)(442)(443)(444).…”
Section: Preventionmentioning
confidence: 99%
“…Additional research is needed to identify what qualities of sibling relationships are linked to ER use and ability. Ravindran et al (2015) suggested that sibling conflict may serve as a context for developing specific ER strategies related to negative affect. Although to date no direct evidence supports a connection between sibling conflict and ER strategy use, indirect support comes from an intervention study by Kennedy and Kramer (2008) involving preschool-and school-age sibling dyads.…”
Section: Sibling Relationships and Emotion Regulationmentioning
confidence: 99%
“…The effect of SAS on parent-focused variables is consistent with research showing secondary gains for programs focused on enhancing sibling relationships. For instance, one study found that mothers and fathers whose offspring participated in a sibling-relationship-building program showed increases in their own emotion regulation skills (Ravindran, Engle, McElwain, & Kramer, 2015). Although additional trials with both clinical and nonclinical samples will be necessary to ascertain sibling-based programs’ effects, the SAS study supports the promise of incorporating siblings into interventions for youth internalizing problems.…”
Section: Implications For Interventionmentioning
confidence: 99%